Lower bound for the area of an analytic curve inside a cube in the space ℂ^n - Ronkin, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The exact lower bound of the area of an analytic curve which lies inside a cube in the space ℂ and passes through its center is obtained.